Humanism, transhumanism and the end of metaphysics: the digital age as the paradigm of the metaphysics of subjectivity - Valle Jiménez, Dune (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper delves into Heidegger's views on humanism and technique. We emphasize his critics to the idea of humanism proposed by the traditional metaphysics that he considers the most prominent expression of Modernity's subject. Heidegger remarks how this idea can be found in Nietzsche's philosophy, mainly in his interpretation of the Power of Will and the Übermensch as the fulfillment, and last stage, of Metaphysics. In this metaphysical Gestell (stage), the human desire to dispose and dominate nature in all its forms expresses the destination of the Being. In the Digital Age, this desire manifests itself in movements like the dataism and Transhumanism, fulfilling the interpretation advanced by the Heidegger more than fifty years ago. The technical-scientific rationality becomes then the enforcement of Metaphysics towards its End.